Narracje głodu czy narracje o głodzie? - Brejnak , Sebastian (Przestrzenie Teorii, 2020)
The aim of this article is to enumerate the main types of discourses in which the phenomenon of hunger is represented. These are following: culture of hunger (an anthropological and ethnological term describing cultural formations based on the problem of famine), politics of hunger (starvation used for political reasons), poetics of hunger (hunger as a component of a piece of art). The question about the difference between the presence of hunger (hunger’s narrative) and the representation of hunger (narrative of hunger) is the main problem of this essay. Brejnak claims that on the one hand, there is no unnarrated hunger (a natural/pure hunger) in cultural communication. On the other hand, he underlines that the experience of hunger as such is non-transitive and verbally inexpressible.